Revaluing paternity; breeding and masculinity in parents post divorce - Zicavo M., Nelson (2012)
Article dealing with the main research findings derived from the study of significant visions of men about the practice of their paternity after divorce, from their own identity constructions of masculinity. The children’s care is the result of sociocultural assignations and power relations in addition to conjugal conflicts conducted wrongly (and legal limitations); this implies for them the impossibility -imposed- to participate in the breeding of their children. The transgression to law regulations related to father and children frequently results in the reduction of the parental link towards diffuse contacts that permit opportunities for manipulations; obstruction and elimination of the father's role, denying the mutual affective necessity and damaging the children's right to rely on both parents for their harmonious breeding.